Biofertilizer And Bioenhancer Concepts For Sustainable Oil Palm Seedling Production. - Ghazali, Amir Hamzah Ahmad; Shamsuddin, Z.H.; Halimi, M. S.; Ramlan, M.F.; Maniah, M. (Universiti Sains Malaysia, 2001)
In oil palm production, nitrogen fertilizer is the most expensive nutrient input required.